Sol-gel fabrication, morphology and magnetic properties of multiferroics BiFe1-xMnxO3 - M.V. Kandaurov; E.V. Vladimirova; A.V. Dmitriev (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2018)
Experimental data on the synthesis and properties of the solid solution BiFe1-xMnxO3 are given. The length of the solid solution (0 ≤ x ≤ 0,20) was established, the morphology of the particles and magnetic properties of the samples were investigated in dependence on the content of a dopant. Nonlinear concentration dependences of magnetic characteristics for BiFe1-xMnxO3 with a maximum at the manganese 5 — 7 mol. %. content were found.